Peningkatan Kompetensi Tata Kelola Keuangan Usaha Mikro Bakso Senggol Desa Pasir Gombong Cikarang Kabupaten Bekasi - Yahya, Adibah; Ayunyngtyas, Eka Avianti; Putri, Lyra Aprilia; Ningrum, Siti Maya (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
Micro, Small and Medium Enterprises (MSMEs) play an important role in reducing poverty by creating jobs. When large enterprises experience difficulties, MSMEs are often the backbone of the economy due to their ability to adapt. Strong MSMEs indicate a growing and resilient regional economy, driving prosperity and reducing economic disparities. However, micro-enterprises often struggle to manage finances and produce accurate financial reports. Limited human resources and financial expertise are obstacles for micro-business owners. The solution is assistance in financial management, especially production costs and preparing financial reports. This programme partnered with meatball traders in Pasir Gombong, Bekasi Regency. The programme implementation included observation, interviews, material provision, mentoring, and monitoring and evaluation from start to finish. The program succeeded in increasing the partners' knowledge competence on financial management so that they could prepare financial reports independently with the help of accounting applications delivered during the mentoring.